Plant Shops Naming Pattern at Cihideung Village, Bandung : A Linguistic Landscape Approach - Hardianto Rahardjo; Ningrum Tresnasari; Nurza Ariestafuri; Raden Novitasari; Uning Kuraesin (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This study discusses the naming pattern of plant shops in Cihideung Village in terms of Linguistic Landscape (LL). LL is a discipline that examines the use of language in public spaces. The purpose of this study is to describe the form and explain the informative function and symbolic function (LL function) in the naming of plant shops in Cihideung Village. The research method used is descriptive qualitative method which produces photographic data from the results of documentation and direct observation. The research object was taken from the names of plant shops located in Cihideung Village. The signs present in the photographic data will then be analyzed using the Landry and Bourhis (1997) model of linguistic landscape theory which divides LL into six levels, namely microlinguistic analysis, language code type analysis, language behavior analysis, psychological analysis, socio-cultural analysis. psychological, and sociological analysis. The conclusion results indicate that the plant shop in Cihideung Village is dominated by shop names that explicitized the type of product using the word florist/florist/flower stall and most of them are composed of Indonesian (monoligual) with the type of lingual unit, namely phrases. Meanwhile, the name of the shop which does not explicitized the type of product is dominated by the identity of the shop owner's name which is composed of Indonesian (monolingual) and in the form of a phrase.